Intensity of judicial review of the European Central banks's supervisory decisions - Magliari, Andrea (Central European Public Administration Review, 2019)
A few years after the establishment of the Single Supervisory Mecha-nism, the General Court of the European Union, in its new supervisory role, annulled for the first time the decisions adopted by the European Central Bank (ECB). These judgments are of particular interest because they allow a preliminary investigation of the intensity of judicial review of the ECB's discretionary choices in the field of banking supervision. This article claims that the first case law of the General Court points to several interesting developments and indicates the resolve to carry out a judicial review which, although adhering strictly to the "limited review" standard, does not shy away from developing judicial techniques to ensure a more incisive scrutiny of the discretion enjoyed by the ECB. Despite the novelty of the issues brought to the attention of the EU judges, it seems possible as a result of this study to envisage, on the one hand, a gradual alignment of the scrutiny of supervisory decisions with those emerged in relation to the Commission's decisions on competition matters. On the other hand, a differentiation from the "light touch" approach adopted in the field of monetary policy can be observed
Keywords: complex economic assessment; court of justice of the EU; European Central Bank; intensity of judicial review; leverage ratio; margin of discretion; supervisory decisions